[Mass graves ; Salvapur-bamur ; Boyoyong clowns [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
The discovery of mass graves by the AFP presents the insurgency and the propaganda war between the AFP and the communists. Mr. Sixto K. Roxas, economist and banker, introduces a new concept in getting communities organized to produce and market their goods in Bacolod. Focuses also on a different kind of clowning like the Boyoyong clowns.